2019
DOI: 10.4269/ajtmh.19-0284
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Cestode Infection Associated with History of Deworming among Primary School Children in Ethiopia

Abstract: Mass deworming of school-aged children with anthelmintics has been recognized as an effective approach for reducing the burden of soil-transmitted helminth (STH) infections. However, the consequences of this intervention on nontargeted parasite populations sharing the same gastrointestinal niche are unclear. We conducted a cross-sectional survey among three primary schools in Sululta town, Ethiopia, to examine the association between students’ histories of deworming treatment in the past 6 months and the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, deworming was only found to have a mitigative effect for STH infections in our multivariate logistic regressions, which is supported by previous literature [ 57 ]. This may suggest that deworming may be creating an environment for other intestinal parasites such as protozoans by mitigating STH infections, as some previous studies have suggested [ 19 ]. In association rule learning, we also observed that having animals such as dogs, cows, horses, and sheep was positively associated with different intestinal parasites, which agrees with previous studies that have found a higher prevalence of intestinal parasitosis among children raising animals compared to those not raising animals [ 58 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, deworming was only found to have a mitigative effect for STH infections in our multivariate logistic regressions, which is supported by previous literature [ 57 ]. This may suggest that deworming may be creating an environment for other intestinal parasites such as protozoans by mitigating STH infections, as some previous studies have suggested [ 19 ]. In association rule learning, we also observed that having animals such as dogs, cows, horses, and sheep was positively associated with different intestinal parasites, which agrees with previous studies that have found a higher prevalence of intestinal parasitosis among children raising animals compared to those not raising animals [ 58 ].…”
Section: Discussionmentioning
confidence: 93%
“…Any remaining fecal samples were analyzed using formol-ether concentration analysis at the Department of Medical Laboratory at Addis Ababa University, Ethiopia. A more in-depth description of each parasitological test can be found in our previously published study [ 19 ]. Allergic disorders related questions were derived from the widely used and validated ISAAC symptoms questionnaire [ 20 ], which had previously been used in this age group of children [ 21 , 22 ] in Ethiopia.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study in three primary schools in Sululta after deworming. [112] (Continued ) examination is not widely practiced and it is not possible to differentiate Taenia eggs based on microscopy [135,147]. More sensitive and specific diagnostic tools need to be used to identify the true prevalence and outline the epidemiology of T. solium.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of H pylori measurements can be found in our previous published studies [ 18 , 19 ]. Briefly, each participant provided a stool and blood sample for H. pylori testing.…”
Section: Methodsmentioning
confidence: 99%